2008
DOI: 10.2337/db07-0874
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tyrosine Phosphatase 2(256–760) Construct as a New, Sensitive Marker for the Detection of Islet Autoimmunity in Type 2 Diabetic Patients

Abstract: OBJECTIVE—The presence of autoantibodies to islet antigens GAD and/or tyrosine phosphatase 2 (IA-2) in type 2 diabetic patients (latent autoimmune diabetes in adults [LADA]) identifies subjects at high risk to develop insulin dependency. The aim of this study was to dissect humoral anti–IA-2 immune response in Caucasian LADA patients, identifying the most sensitive construct to evaluate IA-2 immunoreactivity and comparing LADA IA-2 epitope specificities to those found in type 1 diabetes. RESEARC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…These studies, which for the most part were conducted in patients affected by T1DM and latent autoimmune diabetes of the adulthood (26), have demonstrated that IA-2 antibody responses appear to be primarily directed against the IA-2ic (amino acids 601-979) of the molecule (20, 26 -30). Currently two of these constructs, namely ICA512bdc (amino acids 256 -556; 630 -979) and IA-2ic (amino acids 601-979) in combination with other islet autoantibodies, have been widely used in large scale RIAs in epidemiological studies to classify T1DM patients and identify their at-risk relatives and enroll them in intervention studies aimed at preventing overt disease (16 -18).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, which for the most part were conducted in patients affected by T1DM and latent autoimmune diabetes of the adulthood (26), have demonstrated that IA-2 antibody responses appear to be primarily directed against the IA-2ic (amino acids 601-979) of the molecule (20, 26 -30). Currently two of these constructs, namely ICA512bdc (amino acids 256 -556; 630 -979) and IA-2ic (amino acids 601-979) in combination with other islet autoantibodies, have been widely used in large scale RIAs in epidemiological studies to classify T1DM patients and identify their at-risk relatives and enroll them in intervention studies aimed at preventing overt disease (16 -18).…”
Section: Discussionmentioning
confidence: 99%
“…IA-2 IC , IA-2 256 -760 , ZnT8, and tTG antibodies were measured by previously described radioimmunoprecipitation assays (15,16). TPO and APC antibodies were measured using RIA (Medipan, Berlin, Germany) and ELISA (Axa Diagnostics, Pomezia Italy) commercially available kits, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to IAA and ICA, anti-IA-2 AAbs show no variation with age and thus, when anti-GAD65 autoantibodies are also evaluated, an autoimmune signature of the diabetes can be defined [23] . Recently, antibodies against the IA-2 (256-760) fragment were shown to be a reliable marker in LADA patients and they were positively correlated with higher frequency of autoimmunity and susceptible HLA haplotypes [48] . Patients with autoimmune diabetes are likely to be presented with an additional autoimmune condition of endocrine (thyroid and adrenal glands) or non-endocrine organs (thyroid and adrenal glands) [23] .…”
Section: At Thementioning
confidence: 99%